Teen caregivers living with schizophrenic fathers in West Java - Bakti, Sarah Kusumah; Agustina, Hana Rizmadewi; Sriati, Aat; Suryani, Suryani; Shivji, Noureen Asif (Intelektual Pustaka Media Utama, 2025)
Adolescents with fathers who have schizophrenia are more likely to experience emotional dysregulation, negative decisions, a failure to form an identity, inconsistency in decision-making, and failure to adapt. This study is aimed to investigate the lived experiences of adolescents who live with a father who has schizophrenia in an urban area of Bandung City, West Java. The qualitative phenomenological approach was used in this study. In-depth interviews were conducted with six adolescent participants, aged 13 to 22, who live in Bandung City with a father diagnosed with schizophrenia. The Colaizzi method was then used to analyze the interview transcripts. Data analysis produced eight major themes: i) dealing with psychosocial problems and moral dilemmas, ii) a lack of closeness between father and children, iii) exposures to violence inside and outside the home, iv) getting the wisdom behind the catastrophe, v) changing roles and responsibilities, vi) a lack of social support, vii) difficulties to share personal issues, and viii) seeking to build a better future. The adolescents still have opportunities to continue building a better future. Improving health promotion and education programs to manage negative emotions and developing Self-Help Groups for adolescents whose fathers have schizophrenia is thus necessary.